(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Agricultural sector that is one of the cash-intensive sectors was adversely impacted by cash crunch created by the 2022 demonetization in Nigeria. The agricultural value chain was disrupted with resultant effect of distress sales, wastage of perishable products, labour constraint and reduction in time allotted to farming. Thus, this study examined agricultural produce price differentials before and during demonetization in Anambra State, Nigeria. A three-stage sampling procedure was adopted for the study. Five rural Local Government Areas (LGAs) were purposively selected; Ogbaru, Anambra West, Ihiala, Idemili North and Anaocha followed by a random selection of four villages from each LGA and ten farmers from each village making 200 farmers sampled using structured questionnaires before and during demonetization. The data was then analyzed using mean, frequency, percentages, graph, and inferential statistics-t-testα0.05. The result showed farmers financial inclusion (48%), out of which only (45.83%) who were majorly youth (mean age=34 years) operated digital banking. Before demonetization (94%) farmers used cash for transactions which only reduced to 70.00% during demonetization. Physical bank transaction also dropped from 4.20% to 9.00%, but there was an increase in digital transactions from 2.10% to 24.30%. A significant price differential α0.05 was obtained for all farm produce considered. Market price reduction (75%), Cash constraint (60.50%) and loss of time/ divided attention (58%) were the most severe challenges of the farmers during demonetization. The study recommends that financial institutions should make provision for rural populace especially farmers to easily change their money during demonetization.